Bioefficacy of powdery formula-tions based on kaolin powder and cashew (Anacar-dium occidentale L.) balms to control Callosobruchus maculatus F. (Coleoptera, Chrysomelideae: Bruchidae) in stored cowpea (Vigna unguiculata L.) - Kpoviessi, Dieudonné A.; CHOUGOUROU, CHÈPO DANIEL; BOKONON GANTA, AIMÉ HYPPOLITE; DOSSOU, JOSEPH (My University, 2017)
In this study, the bioefficacy of the powdery formulations were evaluated. Thus powdery insecticide Antouka®, kaolin powder and powdery formulations based on kaolin powder and various cashew balms were tested against, cowpea bruchid in storage. For each balm, it was formulated 10 g of powdery formulation, which were obtained with 10 g of kaolin and 1 mL of cashew balm. Antouka® insecticide was applied at recommended dose; powdery formulations were tested at 0.5 g; 1 g, for 50 g of cowpea seeds in jars. Twenty (20) cowpea weevils at 24 h old were introduced in each jar. The jars, covered with wire mesh, were kept outdoors during forty five (45) days using a randomized block design with four replicates. Therefore, parameters of mortality and F1 progeny of Callosobruchus maculatus, weight losses, seeds damaged and germination rate were assessed. Results obtained indicated that Antouka® insecticide and the formulated powders caused a significant mortality rate and improved the germination rate of seeds. Nevertheless, the cold extracts had less seeds damaged than hot extracts. F1 progeny decreased with increased dose, (25.50±7.96 insects to 44.50±7.67 insects for 0.5 g; and 11.25±4.62 insects to 29.50±3.22 insects for 1 g). According to calculated LD50 and their confidence intervals, formulated powders have significant toxicity on C. maculatus. These results revealed the bioefficacy of powdery formulations. They can be recommended as alternatives insecticides.
Keywords: Callosobruchus maculatus; cowpea; bioinsecticides; toxicity; Benin.